A Case Report on Prosopometamorphopsia - Isuri Wimalasiri; Nimesha Subasinghe; Chathurie Suraweera (BJPsych Open)
Aims: Prosopometamorphopsia is an extremely rare phenomenon where the individual perceives facial distortions in self or others. “Demon face syndrome” and “Alice in Wonderland syndrome” are some lay terms coined to describe this condition.